2022
DOI: 10.1007/s42773-022-00188-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-supported nano-scale zerovalent iron activated persulfate for remediation of aromatic hydrocarbon-contaminated  soil: an in-situ pilot-scale study

Abstract: Biochar supported nano-scale zerovalent iron (nZVI/BC) for persulfate (PS) activation has been studied extensively for the degradation of pollutants on the lab scale, but it was rarely applied in practical soil remediation in the field. In this research, we developed a facile ball-milling method for the mass production of nZVI/BC, which was successfully applied to activate persulfate for the remediation of organic polluted soil on an in-situ pilot scale. In-situ high-pressure injection device was developed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that ROS such as superoxide radical (O 2 • − ), hydroxyl radical (•OH), and singlet oxygen ( 1 O 2 ) might be involved in the oxidation process (Zeng et al 2022;Han et al 2022;Yao et al 2022). Tertbutanol (TBA) was found to be the scavenger for •OH and was used to reveal the role of •OH in phenol removal in the KMnO 4 /BRB system (Luo et al 2019).…”
Section: Reactive Oxygen Species Generation In Kmno 4 /Brb Systemmentioning
confidence: 99%
“…Previous studies have shown that ROS such as superoxide radical (O 2 • − ), hydroxyl radical (•OH), and singlet oxygen ( 1 O 2 ) might be involved in the oxidation process (Zeng et al 2022;Han et al 2022;Yao et al 2022). Tertbutanol (TBA) was found to be the scavenger for •OH and was used to reveal the role of •OH in phenol removal in the KMnO 4 /BRB system (Luo et al 2019).…”
Section: Reactive Oxygen Species Generation In Kmno 4 /Brb Systemmentioning
confidence: 99%
“…To meet specific application requirements, BC produced via slow pyrolysis is typically subjected to milling and sieving, resulting in particle sizes ranging from 0.044 to 20 mm [22]. BC with a finer particle size boasts a larger specific surface area and an increased number of active sites, making it advantageous for applications such as soil remediation and heavy metal adsorption [23][24][25]. However, it is essential to determine whether fine particle size BC similarly benefits cementitious materials.…”
Section: Introductionmentioning
confidence: 99%